2000
DOI: 10.1016/s0271-5317(00)00138-x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants and disease: More questions than answers

Abstract: Reactive oxygen species are widely believed to be involved in the etiology of many diseases as indicated by the signs of oxidative stress seen in those diseases. Conversely, antioxidants are believed to be protective. An important part of the supporting evidence is the consistently-seen inverse association between, on the one hand, intake of B-carotene and vitamin C and of fruit and vegetables, and, on the other hand, risk of cancer and coronary heart disease (CHD). However, the failure of supplemental p-carot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
239
0
17

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 419 publications
(259 citation statements)
references
References 49 publications
3
239
0
17
Order By: Relevance
“…Epidemiological studies have consistently shown that a high dietary intake of fruits and vegetables is strongly associated with reduced risk of developing chronic diseases, such as cancer and cardiovascular disease [38][39][40][41][42]. In fact, the implication of oxidative and nitrosative stress in the etiology and progression of several acute and chronic clinical disorders has led to the suggestion that antioxidants can have health benefits as prophylactic agents [39].…”
Section: Endogenous Antioxidant Defencesmentioning
confidence: 99%
“…Epidemiological studies have consistently shown that a high dietary intake of fruits and vegetables is strongly associated with reduced risk of developing chronic diseases, such as cancer and cardiovascular disease [38][39][40][41][42]. In fact, the implication of oxidative and nitrosative stress in the etiology and progression of several acute and chronic clinical disorders has led to the suggestion that antioxidants can have health benefits as prophylactic agents [39].…”
Section: Endogenous Antioxidant Defencesmentioning
confidence: 99%
“…Organizm człowieka ma system ochronny przed wolnymi rodnikami, który stanowią antyoksydanty endogenne, jednak ważną rolę w zmniejszaniu uszkodzeń oksydacyjnych pełnią antyoksydanty żywieniowe, do których należą między innymi związki fenolowe, witaminy C i E oraz karotenoidy [10,17]. Naturalne przeciwutleniacze zawarte w owocach, warzywach oraz ziołach odgrywają istotną rolę w profilaktyce i leczeniu wielu chorób, w tym chorób cywilizacyjnych [1,10,11,21]. Jedną z ważnych roślin dostarczających zarówno surowca zielarskiego, jak i używanego w przemyśle spożywczym, jest bez czarny (Sambucus nigra L.).…”
Section: Wprowadzenieunclassified
“…Since the consumption of vegetables and fruits is strongly advised by many Governments to reduce the risk of several diseases and functional declines associated with aging (Temple, 2000;Willett, 1994Willett, , 1995, their fermentation might widen the choice for the consumption of these products. Over the years, new and diverse methods for processing fruits have been studied in an effort to minimize production losses, increasing farmers' income, and to introduce new products to the market (Duarte et al, 2010).…”
Section: Introductionmentioning
confidence: 99%